2008
DOI: 10.1210/en.2008-0769
|View full text |Cite
|
Sign up to set email alerts
|

Genes Associated with Membrane-Initiated Signaling of Estrogen and Energy Homeostasis

Abstract: During the reproductive cycle, fluctuations in circulating estrogens affect multiple homeostatic systems controlled by hypothalamic neurons. Two of these neuronal populations are arcuate proopiomelanocortin and neuropeptide Y neurons, which control energy homeostasis and feeding. Estradiol modulates these neurons either through the classical estrogen receptors (ERs) to control gene transcription or through a G protein-coupled receptor (mER) activating multiple signaling pathways. To differentiate between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 68 publications
7
118
0
Order By: Relevance
“…7). Although STX did not affect body weight over this short period of administration, our previous work showed that longer-term treatment significantly reduces post-ovariectomy weight gain in females (32,37). These findings are consistent with the in vitro effects of STX on NPY/AgRP and POMC neurons (21,31,32).…”
Section: E635 Rapid Estrogen Signaling In Npy/agrp Neuronssupporting
confidence: 88%
See 3 more Smart Citations
“…7). Although STX did not affect body weight over this short period of administration, our previous work showed that longer-term treatment significantly reduces post-ovariectomy weight gain in females (32,37). These findings are consistent with the in vitro effects of STX on NPY/AgRP and POMC neurons (21,31,32).…”
Section: E635 Rapid Estrogen Signaling In Npy/agrp Neuronssupporting
confidence: 88%
“…In previous studies, the Gq-mER ligand STX showed a clear anorectic effect in female guinea pigs (37,50). Since our in vitro experiments suggested that STX would also be anorectic in males, we wanted to compare food intake in both sexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations suggest that any such effects may be species or paradigm specific, or, more likely, that they are mediated by signaling pathways activated via ERα-independent mechanisms. As an example, a putative membrane estrogen receptor -a Gq-coupled, membrane-initiated pathway -has been implicated in the anorectic effects of E 2 in hypoestrogenic female guinea pigs (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%